Analysis of the Basic Futsal Technical Skill Level of Azzhazel Club Athletes in Semarang City - Fadhil Faadihilah Novanto; Gustiana Mega Anggita; Lina Lina Farda Andani (ACTIVE: Journal of Physical Education, Sport, Health and Recreation, 2026)
The purpose of this study was to determine the level of basic futsal technical skills of the Azzhazel Club athletes in Semarang City. The method used was a survey with test and measurement techniques. Through tests and measurements, objective data will be obtained. The subjects of this study were 20 athletes from the Azzhazel Club in Semarang City. Data collection was carried out through observation and tests. Data analysis was carried out descriptively quantitatively. The results of this study were declared "quite good" by 15 athletes (75%). This means that the futsal skill level of the Azzhazel Club athletes in Semarang City is included in the fairly good level, while the average. The average score of 48.3119 is in the "moderate" range. This can be used as a consideration for coaches or trainers to improve physical and psychological quality, develop strategies, techniques, and playing patterns, and improve the futsal abilities and skills of the Azzhazel Club athletes in Semarang City. The conclusion of this study is that there has been an increase in basic futsal technical skills among the Azzhazel Club athletes in Semarang City.